Employee willingness to work with Robotics in retail pharmacies in South Africa - Khosa, Curtis Kulani (University of the Witwatersrand, Johannesburg, 2022)
The increase in competitiveness in the world of business in retail sector has pushed businesses to adopt advanced technology to have a competitive advantage over their competition. The support of employees through the transition process is crucial to facilitate a smooth process, buy in by employees is of paramount importance so that efficiency and adoption could be achieved easily by the company. This study looks specifically at retail pharmacy environment; therefore, it is important to examine the factors affecting employee willingness to work with robotics in retail pharmacy environment in South Africa. Although studies have been done to examine employee willingness to work with automation, but few have been done specifically looking at the factors influencing employee willingness to work with robotics in the retail pharmacy environment in South Africa. The present study undertakes a quantitative approach in which pharmacy assistants and pharmacists are targeted and online surveys are distributed amongst them to explore the factors influencing employee willingness to work with robotics in retail pharmacies in South Africa. The findings support all eight proposed hypotheses, which are explained in detail in the following chapters below. The contribution of this paper is threefold, contextual, theoretical, and strategical knowledge which each is explained in detail towards the end of the paper
A research report submitted in fulfillment of the requirements for the degree of Master of Business administration , Wits Business school University of the Witwatersrand, Johannesburg, 2022
Keywords: UCTD; SDG-8: Decent work and economic growth